Diagnosing Zygosity in Giant Panda Twins Using Short Tandem Repeats. (30th October 2018) - Qiao, Maiju; Zhou, Yingmin; Connor, Thomas; Li, Rengui; Tang, Dan; Zhang, Hemin; Ran, Jianghong
Abstract : The giant panda, native to mountains of south-west China, is one of the world's rarest bear species and is subject to considerable conservation effort. In captivity, the proportion of twins accounts for 54% of the total number of births. To date, little is known about zygosity in panda populations — specifically, the proportion of monozygotic and dizygotic twins. In this study, we used 10 microsatellite markers for reliable zygosity testing, and the probability of monozygotic twins was 99.963% when all 10 markers were concordant. Out of 43 studied twin pairs, no MZ twins were found, indicating that there may be no identical panda twins (or the incidence is very low). We speculate that the fertilized eggs of giant pandas do not have the capability to split into two identical embryos, or that this ability is very poor, which is likely due to delayed implantation that is common in bear species. The results of this study deepen our understanding of giant panda breeding, yield insight into panda twins' likely mechanism of formation, and reduce the uncertainty of individual identity in wild population surveys.